A new six‐dimensional hyperchaotic system and its secure communication circuit implementation. (25th March 2019) - Wang, Jing; Yu, Wenxin; Wang, Junnian; Zhao, Yanming; Zhang, Jing; Jiang, Dan
Summary: In the paper, a novel six‐dimensional hyperchaotic system is proposed for secure communication. A detailed analysis of some relevant features, such as equilibrium stability, dissipation, bifurcation, and Lyapunov exponents. The results show that there are hyperchaos, chaos, quasi‐periodic, and periodic dynamic behaviors for our constructed hyperchaotic system. Then the six‐dimensional hyperchaotic system is simulated and implemented, which verified its physical realizability. The six‐dimensional hyperchaotic system is applied to complete the signal encryption and decryption circuit design, then the circuit is tested. The results indicate that the proposed hyperchaotic system can play an important role in some key areas such as communication security and complex systems. Abstract : In this paper, a new six‐dimensional hyperchaotic system is proposed, and some related features such as equilibrium stability, dissipation, bifurcation, and Lyapunov exponent are analyzed in detail. Then the six‐dimensional hyperchaotic system is simulated and implemented, which verified its physical realizability. The six‐dimensional hyperchaotic system is applied to complete the signal encryption and decryption circuit design, and then the circuit is tested.